Toward a Framework for Assessing Private vs Public Investment in Infrastructure - Mapila, Kopo Gary; Mölders, Florian; Lauridsen, Morten Lykke (International Finance Corporation, Washington, DC, 2018)
Significant additional resources from the private sector will be needed for infrastructure in emerging market countries if the Sustainable Development Goals are to be achieved. Close to 80 percent of all infrastructure investments are government funded in these countries, yet it is recognized that public sector investments alone will not be sufficient to bridge the infrastructure gap. Scaling up the role that private firms and investors play in infrastructure provision will require a better understanding of the advantages and disadvantages of public versus private provision, including the issues and incentives that need to be considered in order to find the right balance between the two.